THE INFLUENCE OF LEARNING MANAGEMENT AND PRINCIPALS MANAGEMENT SKILL ON SMPIT IBNU ABBAS TARAKAN TEACHERS PERFORMANCE - nuraeni (BAIK Publishers, 2024)
The purpose of this study was to determine the effect of learning management and principal management skills on teacher performance at SMPIT Ibnu Abbas Tarakan. The research method used in this research is descriptive with a quantitative approach. The population amounted to 58 people, so the sampling technique was used with the saturated sample method and the number of samples obtained in this study were 58 respondents. Data analysis techniques using multiple linear regression The results showed that: There is a positive and significant effect of learning management variables and management skills of principals on teacher performance SMPIT Ibnu Abbas Tarakan. This is evidenced by the value of Fcount > Ftable which is 27.262 > 3.12 with a probability value (significance) = 0.000 which is below 0.005.